Membangun SDM Kreatif dan Produktif dengan Memanfaatkan Media Market Place untuk Memulai Bisnis di Masa Pandemic Covid-19 - Retnowati, Ayu Nike; Astria, Nenden (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
MSMEs as small businesses that support the economy can support the equal distribution of community well being. The Covid-19 pandemic has had a negative impact on the economy of the people in Indonesia, such as increasing unemployment and poverty rates and disruption to the trade sector, especially for small traders who run their businesses traditionally. Sukapura Village, Kiaracondong District, Bandung City, West Java, is a village that has 19 RW and 109 RT. Sukapura Village is a village that has residents who are MSME activists. The restrictions on activities during the Covid-19 pandemic have negatively impacted MSME activists financially and in terms of business stability. MSMEs in Sukapura Village consist of food, clothing, grocery wholesalers, etc. The presence of Covid-19 has caused many MSME activists to be affected, namely problems in decreasing income, difficulties for MSME activists to be able to adapt to new conditions due to lack of knowledge about technology in doing business, especially for MSME activists 40 years old above. Another problem is the lack of knowledge in HR management and financial management which is still mixed between personal and business finances. This community service activity aims to increase the understanding of MSME activists by providing socialization regarding the use of market place media for business continuity during the Covid-19 pandemic and capturing business opportunities in this less than ideal situation so that they can optimize income. After conducting socialization, the community is guided to create an account on the marketplace and is inspired to innovate to bring out creativity in the products they have to increase their selling value.